Quantification of protein-protein interactions within membranes by fluorescence correlation spectroscopy - Bleicken, Stephanie; Otsuki, Miki; García-Sáez, Ana J. (Current protein & peptide science, 2011)
The characterization of interactions between membrane proteins as they take place within the lipid bilayer poses a technical challenge, which is currently very difficult and, in many cases, impossible to overcome. The recent development of a method based in the combination two-color fluorescence cross-correlation spectroscopy with scanning of the focal volume allows the detection and quantification of interactions between biomolecules inserted in biological membranes. This powerful strategy has allowed the quantitative analysis of diverse systems, such as the association between proteins of the Bcl-2 family involved in apoptosis regulation or the binding between a growth factor and its receptor during signaling. Here, we review the last developments to quantify protein/protein interactions in lipid membranes and focus on the use of fluorescence-correlation-spectroscopy approaches for that purpose.
Gesehen am 30.03.2022